The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/nu10111714
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nutrient and Food Group Intakes across Sex, Physical Activity, and Body Mass Index in an Urban Brazilian Population

Abstract: The burden of preventable diet-related diseases is significant and becoming worse. Thus, accurately assessing food intake is crucial to guide public health policies and actions. Using food dietary recalls, we evaluated usual dietary intake according to physical activity and nutritional status in an adult urban population from Brasília, Brazil. The usual nutrient and energy intakes distributions were estimated using the Iowa State University (ISU) method. Energy and nutrient intakes were stratified by gender, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 31 publications
4
36
0
1
Order By: Relevance
“…Moreover, the present study revealed that the consumption of meat and sweets and sugars was also much higher compared to that shown by previous research performed among an adult Polish population [3]. In another study, Sousa and Da Costa [12] revealed that the Brazilian adult population consumed fruits and cereals in the highest amounts and indicated a very high consumption of meat and sugars, which is in agreement with the results of the present study.…”
Section: Distribution Of Food Groupssupporting
confidence: 92%
See 4 more Smart Citations
“…Moreover, the present study revealed that the consumption of meat and sweets and sugars was also much higher compared to that shown by previous research performed among an adult Polish population [3]. In another study, Sousa and Da Costa [12] revealed that the Brazilian adult population consumed fruits and cereals in the highest amounts and indicated a very high consumption of meat and sugars, which is in agreement with the results of the present study.…”
Section: Distribution Of Food Groupssupporting
confidence: 92%
“…Daily intake of particular elements was compared with the actual Polish dietary reference intake standards defined by the National Institute of Food and Nutrition [18], which are mandatory for the adult population in Poland. The daily sodium intake was compared to the value of adequate intake (AI), and the intake of three other macroelements was compared to the estimated average requirement (EAR), which is considered the most appropriate to compare the average intake level in the population [12,[18][19][20][21][22]. Obtained results showed that meat and meat products contribute to almost 38% of sodium intake among men and 32% among women.…”
Section: Dietary Intake Of Macroelements With Major Food Groupsmentioning
confidence: 99%
See 3 more Smart Citations